66 The Management of Syncope on the Acute Medical Take. An Experience at a District General Hospital. (6th June 2015) - Young, William; Ibrahim, Maria; Gall, Nicholas
Abstract : Introduction: Syncope accounts for up to 6% of admissions annually. 1 In the over 65 age group, 23% will have an episode of syncope over a 10 year period with a 30% recurrence rate over two years. 2 Up to 60% of patients presenting to A&E with syncope are admitted, however only 50% will have syncope specific investigations and only 50% will receive a final diagnosis. 2 Financial restraints and bed pressures in the UK have increased the need for effective management of syncope. We aimed to assess the management of syncope on the acute medical take. Method: An audit was devised to evaluate the management of patients referred to the medical team over a 50-day period. The medical notes of patients meeting the inclusion criteria were sourced, retrospectively analysed and compared with current NICE guidelines. The project was extended to assess whether development of a pathway with same day syncope services would impact hospital bed stays. Results: Of 190 patients, 77 randomly sourced notes were analysed; 35 patients were identified as having had a syncopal event. 63% were female and the average age was 85 years (67–98). 11% of patients had a full history recorded and only 3% had a complete initial assessment including history, ECG and postural blood pressure recording. 51% of patients had CT brain imaging of which 74% were not indicated. 34% of patients had 24 h ECG monitoring of which none were indicated and no significant result identified. 29% of patients did not have an inpatient echocardiogram and 34% of patients did not have an inpatient cardiology review despite indications. 37% of patients were discharged with no diagnosis. 29% of all patients had previously been admitted with a similar presentation. 46% of patients admitted could have been discharged on the same day had rapid ECHO, cardiology review and injectable loop recorder services been available. This accounts for 160 days of inappropriate hospital stay and with extrapolation, 1168 days in one year. Thus, 3.2 extra beds could be made available at our DGH. Conclusion: The initial assessment of syncope is inadequate and investigations are inappropriately requested or not considered. A proportion of patients do not receive a diagnosis and are unnecessarily admitted. A considerable number of bed days could be prevented with a clear syncope pathway including same day ECHO, cardiology review and injectable loop recorder service, thus relieving pressures on acute medical beds and accident and emergency services. This problem is not unique to our trust and represents a pattern currently prevalent across the UK and further afield. References: Shen WK, Decker WW, Smars PA, et al . Syncope Evaluation in the Emergency Department Study (SEEDS): a multidisciplinary approach to syncope management. Circulation 2004;110(24):3636-45 Lipsitz L, Wei JY, Rowe JW. Syncope in an elderly, institutionalised population: prevalence, incidence, and associated risk. Q J Med. 1985;55(216):45-54